Teaching foreign languages: A challenge to ecuadorian bilingual intercultural education - Haboud, Marleen (International Journal of English Studies, 2009)
Since the Universal Declaration of Linguistic Rights in 1996, there is a tendency not only to maintain linguistic and cultural diversity worldwide, but also to ease universal access to quality education which should comprise the learning of other languages and cultures and the generation of intercultural relations. In this sense, this article discusses the right that minoritized peoples in Ecuador have to learning other languages while reinforcing their own. After describing briefly the Ecuadorian main linguistic and educational policies in regards to the teaching of foreign languages, this article analyses the contrasting viewpoints of indigenous and non indigenous peoples towards the process of teaching-learning foreign languages. Finally, it offers some suggestions and general parameters related to foreign language teaching in the multilingual context of the study.